2020
DOI: 10.1177/2058738420950593
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of oxidative stress and NLRP3 inflammasome by Saikosaponin-d alleviates acute liver injury in carbon tetrachloride-induced hepatitis in mice

Abstract: NLRP3 inflammasome activation results in severe liver inflammation and injury. Saikosaponin-d (SSd) possesses anti-inflammatory and hepatoprotective effects. This study aimed to determine the protective effects of SSd on carbon tetrachloride (CCl4)-induced acute liver injury in mice, and whether oxidative stress and NLRP3 inflammasome activation participate in the process. The CCl4 mice model and controls were induced. The mice were treated with SSd at 1, 1.5, or 2.0 mg/kg in a total volume of 100 µl/25 g of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…Furthermore, studies have shown that SSd can inhibit the activation of HSCs by regulating intracellular inflammatory responses, thereby eventually inhibiting liver fibrosis ( Chen et al, 2013 ). Our previous studies also confirmed that SSd had a protective effect on CCl 4 -induced acute liver injury ( Chen et al, 2020 ). CCl 4 -induced chronic liver injury and liver fibrosis model mice were treated with SSd, and found that liver injury and liver fibrosis were significantly alleviated by SSd treatment compared with the control group.…”
Section: Discussionsupporting
confidence: 78%
“…Furthermore, studies have shown that SSd can inhibit the activation of HSCs by regulating intracellular inflammatory responses, thereby eventually inhibiting liver fibrosis ( Chen et al, 2013 ). Our previous studies also confirmed that SSd had a protective effect on CCl 4 -induced acute liver injury ( Chen et al, 2020 ). CCl 4 -induced chronic liver injury and liver fibrosis model mice were treated with SSd, and found that liver injury and liver fibrosis were significantly alleviated by SSd treatment compared with the control group.…”
Section: Discussionsupporting
confidence: 78%
“… 17 A study by Chen et al showed that SSD alleviated acute liver injury in carbon tetrachloride (CCl4)-induced hepatitis by suppressing oxidative stress and activation of the NLRP3 inflammasome. 18 Su etal demonstrated that SSD effectively improved lipopolysaccharide (LPS)-induced inflammation-related depressive behaviors. 19 However, the function of SSD in lytic bone disease remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…mtROS levels in liver tissues of septic mice were measured by MitoSOX™ Red reagent (Thermo Fisher, USA) as described in a previous study [ 42 , 43 ]. Briefly, 5 μ M MitoSOX™ reagent working solution was prepared.…”
Section: Methodsmentioning
confidence: 99%